Penerapan Terapi Mengisap Es Batu untuk Mengurangi Keluhan Haus pada Pasien Chronic Kidney Disease (CKD) dengan Pembatasan Cairan - Effrilia, Frinanda; Kurniawan, Wasis Eko (CV. ALIM'SPUBLISHING, 2026)
Chronic kidney disease is a progressive decline in kidney function that leads to fluid and electrolyte imbalance, requiring fluid restriction which often causes thirst and may result in ineffective peripheral perfusion. One non-pharmacological nursing intervention that can be applied is the ice cube sucking technique as part of fluid management. This study aimed to analyze the implementation of education the ice cube sucking technique in improving fluid management and peripheral perfusion in elderly patients with chronic kidney disease. The study used a descriptive case study design with a nursing process approach conducted over three sessions in an elderly patient with chronic kidney disease. The intervention was delivered in three sessions, each lasting approximately 15–20 minutes. The results showed a reduction in thirst complaints, improvement in peripheral perfusion indicated by capillary refill time of less than 2 seconds and warm extremities, as well as increased patient and family ability in managing fluid intake. In conclusion, the ice cube sucking technique are effective nursing interventions in fluid management and improving peripheral perfusion in patients with chronic kidney disease.